Female characters in the novels by V.S. Naipaul - Steidlová, Veronika (2007)
This thesis examines the female characters in the novels "The Mystic Masseur", "The Suffrage of Elvira" and "A House for Mr Biswas" by a Trinidadian writer V.S. Naipaul. I compare the main female characters in these novels, considering their social standings, their relationships with other characters, especially the male ones, and the attitudes towards their positions in Hindu society. I have found out that women in these Naipaul's novels lead very similar lives, they are presented as unique personalities and as the more practical and sensible parts of marriages.